2017
DOI: 10.21010/ajtcam.vi15.1.4
|View full text |Cite
|
Sign up to set email alerts
|

ESSENTIAL OIL OF THYMUS PECTINATUS FISCH&MEY.VAR.PECTINATUS: CHEMICAL FORMATION, ANTIMICROBIAL, ANTIOXIDANT, ANTISPASMODIC AND ANGIOGENIC ACTIVITIES

Abstract: Background: Thymus species are well-known as medicinal plants. It was aimed to investigate the chemical composition of Thymus pectinatus (TP) and its antioxidant, antimicrobial, antispasmodic, and angiogenic activities. Materials and Methods: After essential oil of TP (EO-TP) was obtained with clevenger distillation system, it was analyzed for chemical composition with GC-MS. To study antispasmodic activity, eight male Wistar albino rats each weighing approximately 250-300 g were used. Results: The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Thymus species are known for their antibacterial activities, which are attributed to secondary plant metabolites, polyphenols, and essential oils. 63,64 Contrary to the results, it was previously reported in the literature that the methanol extract of TP showed no (or very little) antimicrobial activity. 33 The main compound of the TP and TC extracts is rosmarinic acid (144 mg/g extract and 163 mg/g extract respectively) followed by quinic acid (34 mg/g extract and 65 mg/g extract respectively).…”
Section: Antibacterial Activitycontrasting
confidence: 70%
See 2 more Smart Citations
“…Thymus species are known for their antibacterial activities, which are attributed to secondary plant metabolites, polyphenols, and essential oils. 63,64 Contrary to the results, it was previously reported in the literature that the methanol extract of TP showed no (or very little) antimicrobial activity. 33 The main compound of the TP and TC extracts is rosmarinic acid (144 mg/g extract and 163 mg/g extract respectively) followed by quinic acid (34 mg/g extract and 65 mg/g extract respectively).…”
Section: Antibacterial Activitycontrasting
confidence: 70%
“…They were used as spices and for seasoning of meatballs by local communities. Previous studies have reported the chemical composition and antioxidant, anticancer, antifungal, antispasmodic, and angiogenic activities of the essential oil of TP and TC 30‐34 . However, there are limited studies in the literature on the extracts of these plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These synthetic substances may adversely affect health or cause certain diseases (Chan,1987;Barlow, 1990). In recent years for this reason, there is a growing interest in studies of natural additives as potential antioxidants as a natural additive for some plant extracts and essential oils is intended to use (Reynolds, 1996;Tepe et al, 2004;Akkuş-Çetinus et al, 2007;Tepe et al, 2016;Göze Saygın et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils of the plants which are widely use as alternative remedies for the treatment of many diseases and natural therapies and pharmaceutical alternative medicine have been gain great interest (Tepe et al, 2004;Akkuş-Çetinus et al 2007;Tepe et al, 2016;Göze Saygın et al, 2018).…”
Section: Introductionmentioning
confidence: 99%